Peningkatan Pertumbuhan Tanaman Sawi Pakcoy dengan AB Mix dan Zat Pengatur Tumbuh pada Hidroponik Sistem Sumbu - Agus Miftakhurrohmat; M Abror; Alfianita Febri Roudhotul Jannah (Fakultas Pertanian, Universitas Timor, 2023)
The purpose of this study was to determine how to increase the production of mustard pakchoy on the provision of AB mix nutrition and growth regulators in the hydroponic system of the axis. This study was conducted from January to March 2022. This study used a factorial randomized block design (RAK), namely the first factor was the dose of AB mix nutrition which consisted of three levels, namely 25%; 50%; 75% and 100%. The second factor is the concentration of growth regulators consisting of three levels, namely 1cc, 2cc and 3cc. The total treatment combination resulted in 12 treatment combinations. Each treatment was repeated 3 times to produce 36 experimental units. Observation variables include plant height, stem diameter, number of leaves, wet weight and dry weight of the plant. The results showed that there was a significant interaction on the observed variables of wet weight, dry weight and number of leaves at the age of observation 7 and 21 days after planting and stem diameter at the age of 7 days after planting. The observation of plant height did not provide a significant interaction but each treatment gave a significant response at the age of 21 and 35 days after planting. The dose of ZPT 2cc gave the highest value for the variable plant height at the age of observation 21 and 35 days after planting.